Produksi Serasah Daun Mangrove di Pulau Manomadehe Kecamatan Jailolo Selatan Kabupaten Halmahera Barat - Khoirunisa; Salim Abubakar; Mesrawaty Sabar (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2022)
The mangrove ecosystem is one of the ecosystems with high productivity due to the input of organic matter from litter. Litter production is the main supporter of fisheries potential, namely as a food source for aquatic biota. On Manomadehe Island, the community still continues to cut down mangroves to be used as firewood and building materials. Activities like this will result in damage to the mangrove forest and a decrease in the amount of litter production. Research objectives 1. To determine the amount of mangrove leaf litter production on Manomadehe Island, South Jailolo District, West Halmahera Regency. 2. Knowing the rate of decomposition of mangrove leaf litter on Manomadehe Island, South Jailolo District, West Halmahera Regency. This research was carried out in June-August 2020 using the purposive sampling method to determine stations, density (line transect plot), and litter-trap litter production. In general, the composition of mangrove species found at the study site on Manomadehe Island consisted of 3 families with 6 species (Rhizophora stylosa, Rhizophora apiculata, Rhizophora mucronata, Sonneratia alba, Avicennia marina, Avicennia lanata). Total production of mangrove leaf litter is 1276,59 grams/m2/60days, the highest is at Station 1 589,80 grams/m2/60days, Station 2 is 419,59 grams/m2/60days, Station 3267,21 grams/m2/60days. The highest litter contributor was Rhizophora stylosa 424,25 grams/m2/60days. Rhizophora apiculata 340,79 grams/m2/60days, Sonneratia alba 336,94 grams/m2/60days, Rhizophora mucronata 99,26 grams/m2/60days, Avicennia lanata 38,55 grams/m2/60days, Avicennia marina species are 36,80 grams/m2/60days.